1993
DOI: 10.1083/jcb.120.2.523
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of integrins alpha 3 beta 1 and alpha 2 beta 1: potential role in keratinocyte intercellular adhesion.

Abstract: Abstract. The colocalization of integrins ot2/~ and ot3fl~ at intercellular contact sites of keratinocytes in culture and in epidermis suggests that these integrins may mediate intercellular adhesion (ICA). P1B5, an anti-u3fl~ rnAb previously reported to inhibit keratinocyte adhesion to epiligrin, was also found to induce ICA. Evidence that P1B5-induced ICA was mediated by a2/3~ and O/3/~1 was obtained using both ICA assays and assays with purified, mAb-immobilized integrins. Selective binding of ot2/3~-coated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
1
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(121 citation statements)
references
References 33 publications
10
109
1
1
Order By: Relevance
“…Previous studies suggested that ␤1 integrins can mediate cell-cell adhesion via homophilic or heterophilic integrin-integrin interactions involving ␣2␤1, ␣3␤1, and ␣4␤1 (27)(28)(29)35), whereas our data indicate the involvement of AJs. The role of ␤1 integrins in cell-cell adhesion was questioned, because a blocking anti-␤1 mAb did not interfere with intercellular junction organization (36).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Previous studies suggested that ␤1 integrins can mediate cell-cell adhesion via homophilic or heterophilic integrin-integrin interactions involving ␣2␤1, ␣3␤1, and ␣4␤1 (27)(28)(29)35), whereas our data indicate the involvement of AJs. The role of ␤1 integrins in cell-cell adhesion was questioned, because a blocking anti-␤1 mAb did not interfere with intercellular junction organization (36).…”
Section: Discussioncontrasting
confidence: 56%
“…Thus, in this experimental setup, clustering of both Ln-5-binding integrins ␣3␤1 and ␣6␤4 can increase E-cadherin homophilic interactions in the three cell types tested. An involvement of integrin ␣3␤1 in mediating cell-cell adhesion has been demonstrated before (27)(28)(29). However, these are the first results indicating that AJs play a role in this process.…”
Section: Ligation Of ␣6␤4 Triggers Stronger Cell-cell Aggregationmentioning
confidence: 42%
“…The type I collagen-binding receptor, ␣2␤1, is constitutively expressed on keratinocytes (22,23), and as we reported recently, this integrin transduces collagen-mediated induction of collagenase-1 (5). Similarly, collagen stimulates collagenase-1 expression in fibroblasts via ligand binding to ␣2␤1 (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…The alpha2 and alpha3 subunits were found at the basal domain of intestinal cells according to strict complementary staining patterns along the crypt-villus axis, the alpha2 subunit being predominant in the crypts and alpha3 on the villus (62,82,86). It is noteworthy that both of these subunits were also localized at the lateral domain of enterocytes, where they can serve as mediators of intercellular adhesion (92), and that the population of cells exhibiting this lateral staining extends beyond the crypt and villus compartments for the alpha2 and alpha3 subunits, respectively (6). On the other hand, the alpha6 subunit was uniformly distributed at the base of epithelial cells from the bottom of the crypt to the tip of the villus (62, [80][81][82]93).…”
Section: Integrin Expression and Distribution In The Human Small Intementioning
confidence: 99%